Enhancing Dignity for Older Inpatients: The Photograph-Next-to-the-Bed Study. Issue 5 (20th October 2018) - Hubbard, Ruth E.; Bak, Melissa; Watts, Jacqueline; Shum, David; Lynch, Angelica; Peel, Nancye M.
ABSTRACT: Objectives : Older inpatients compromised by illness and cognitive decline may be stripped of physical and cultural identifiers, making them vulnerable to erosion of dignity. This study explored the experiences of patients, carers and clinical staff in response to a simple intervention that could enhance the dignity of care for older inpatients. Methods : All patients in a rehabilitation ward were encouraged to have a photograph of themselves next to their bed. Of those who participated, focus groups were recruited for patients, family members and staff to explore their reflections. Discussions were transcribed and analyzed using a deductive approach to capture evolving themes relating to patient care. Results : All groups reported that the photograph provided "connection" and means of communication between patients and staff. Staff spoke positively of gaining additional insights into patients' lives. Benefits included enrichment of inter-personal relationships between patients and staff, between staff and families and between patients themselves. Conclusions : A bedside photograph improved connections between staff, patients and carers, promoting patients' dignity of identity. Clinical Implications : Displaying a bedside photograph as a visual reminder of the patient in the pre‑illness state helps preservation of an individual's dignity, a core concept in patient‑centered care.